Pajak Kendaraan Listrik dan Infrastuktur: Insentif atau Hambatan bagi Pertumbuhan Industri Kendaraan Ramah Lingkungan? - Timothy Tanujaya; Dika Fuji Okta; Edy Sarwono; Uun Sunarsih (Universitas Muhammadiyah Surabaya, 2025)
This article examines how tax laws related to electric vehicles (EVs) and infrastructure can encourage or hinder the expansion of the green car sector. Favorable tax policies, such as tax exemptions and subsidies, have been shown to significantly increase EV adoption in a number of countries, including China, Indonesia, the United States, and Norway. Norway is one of the countries with the highest EV penetration rates in the world, which has effectively promoted EV adoption through generous tax incentives. On the other hand, EV market expansion is hampered in developing countries such as Indonesia by inconsistent policies and inadequate infrastructure. The results suggest that effective tax laws and infrastructure support can promote EV adoption and help nXCachieve international emission reduction goals. The study’s recommendations include establishing emission-based tax laws, funding charging stations, and maintaining consistent policies over the long term to facilitate the shift to greener modes of transportation.